2004
DOI: 10.1523/jneurosci.5561-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Glucose Metabolism Induce Hypothermia Leading to Tau Hyperphosphorylation through Differential Inhibition of Kinase and Phosphatase Activities: Implications for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) brains contain neurofibrillary tangles (NFTs) composed of abnormally hyperphosphorylated tau protein.Regional reductions in cerebral glucose metabolism correlating to NFT densities have been reported in AD brains. Assuming that reduced glucose metabolism might cause abnormal tau hyperphosphorylation, we induced in vivo alterations of glucose metabolism in mice by starvation or intraperitoneal injections of either insulin or deoxyglucose. We found that the treatments led to abnormal tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
208
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 68 publications
17
208
3
2
Order By: Relevance
“…Further, there may be selective vulnerability of different brain regions to various pre-and postmortem factors as Bag 1 in the cerebellum was not significantly affected by 4 hr of postmortem delay. This latter finding is consistent with the view that the cerebellum is not affected by reduced metabolism and that certain cerebellar proteins (e.g., phosphatases) have an intrinsic resistance to hypothermia as well (Planel et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, there may be selective vulnerability of different brain regions to various pre-and postmortem factors as Bag 1 in the cerebellum was not significantly affected by 4 hr of postmortem delay. This latter finding is consistent with the view that the cerebellum is not affected by reduced metabolism and that certain cerebellar proteins (e.g., phosphatases) have an intrinsic resistance to hypothermia as well (Planel et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that there is evidence linking aspects of low body temperature (∼29 °C) and cell dysfunction in animal models of neurodegenerative diseases (Planel et al, 2004). More specifically, abnormal tau hyperphosphorylation in the hippocampus is associated with hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been demonstrated that insulin activates the same signaling pathway leading to phosphorylation of Akt and GSK3 in brain as in peripheral tissues. Thus, injection of insulin increased GSK3 phosphorylation in mouse brain [131] and brain GSK3 phosphorylation was reduced by blockade of insulin signaling by knockout of the insulin receptor [132] and in mice with dietinduced insulin-resistance [133]. It is important to note that glucose levels were not changed in these latter two studies, because glucose levels were recently found to also regulate GSK3 phosphorylation.…”
Section: Diabetes and Gsk3mentioning
confidence: 89%
“…Since glycolysis is the main source of ATP production in brain, impairment of glycolysis may lead to shortage of ATP in brains, thus to cellular dysfunction (74,271). Moreover, decreased ATP shortage can also induce hypothermia, causing abnormal tau phosphorylation through differential inhibition of kinases and phosphatases (311).…”
Section: Identification Of Carbonylated Proteins In Brainmentioning
confidence: 99%